THE EFFECT OF BLOOD HERB (CHISTOTEL) (CHELIDOII HERBA) AND ALOE EXTRACT ON THE INFLAMMATION PROCESS (Conferencea, 2024)
In this article, it was determined that the drugs have anti-inflammatory effects by using a 1:3 water solution of bloodroot (chistotel) and aloe extract in the treatment of artificially induced inflammatory processes in white mice, and the experimental results of their use in the treatment of pathological processes are described.